The Role of the Internal Audit Function in Moderating the Effect of Audit Committee Gender Diversity on Audit Quality - Kurniawansyah, Deddy; Iswajuni, Iswajuni (JASa (Jurnal Akuntansi, Audit dan Sistem Informasi Akuntansi), 2025)
This study examines how gender diversity on the audit committee board affects audit quality, with the internal audit function serving as a moderating factor. The study analyzed 321 firm-year observations based on the annual reports of manufacturing firm listed on Indonesia Stock Exchange listed between 2019 and 2023. This study uses PLS-SEM to examine a research hypothesis. Our findings provide new insights to describe that the resence of women makes the audit committee more diverse and able to have a higher impact on audit quality. They have high performance standards to demonstrate the importance of the audit committee's responsibility in the financial reporting and management monitoring process. The internal audit function has strengthened the effect of a gender diversity on audit quality. Theoretically, this study contributes to the development of literature related to agency theory. For potential investors, as a strategy, invest in companies that have quality audits due to the strong encouragement from companies with more gender-diverse audit committees. For the government, strengthen the policy of women leadership on corporate boards to improve good governance.